THE EFFECT OF SERVICE QUALITY AND PRICE ON CUSTOMER SATISFACTION ON THE SHOPEE APPLICATION - Devina Amelia; Haris Maupa; Andi Nur Baumassepe (Paulus Journal of Accounting (PJA), 2023)
Companies must be able identify the most suitable marketing strategy for their business in order to thrive and accomplish their main objectives. Shopee is one of the first and leading e-commerce enterprises among Indonesian consumers. Customer satisfaction is the most essential concept in the business sector since it is utilized to attract customers. Customer satisfaction is occasionally dependent on service quality and price. The purpose of this study is to analyze the effect of service price and quality on customer satisfaction in the Shopee app. The quantitative research approach combines with descriptive and verification methods in the study. The study begins in February-April 2023 at Pasundan University's Faculty of Economics and Business in Bandung, West Java. The proportional random sampling technique was employed to obtain samples among 100 students. The data was collected using a questionnaire with a Likert scale that was filled out directly by the respondents. Data were analyzed using a hypothesis testing test that began with the F test (ANOVA), t test, and analysis of the Coefficient of Determination (R2). According to the test results, service quality and pricing have a significant effect on customer satisfaction. As a result, Shopee should continue to enhance the services that it offers to customers in order to attain high customer satisfaction and sell products at affordable prices.